DEVELOPMENT TRENDS AND DIRECTIONS OF ADAPTATION OF AGRO-INDUSTRIAL ENTERPRISES TO GLOBAL CHANGES (INNOVATIVE ECONOMY, 2026)
Voloshchuk Yu.O., Voloshchuk V.R.  DEVELOPMENT TRENDS AND DIRECTIONS OF ADAPTATION OF AGRO-INDUSTRIAL ENTERPRISES TO GLOBAL CHANGESPurpose. The aim of the article is to study modern trends in the development of agro-industrial enterprises and to substantiate the key areas of their adaptation to global changes, taking into account economic, environmental and institutional factors of influence.Methodology of research. The work uses induction and deduction methods to identify trends in the development of the agricultural sector and establish cause-and-effect relationships; analysis and synthesis methods to generalize scientific approaches and compare the development of the agricultural sector of Ukraine and EU countries, in particular Poland. The abstract and logical method is used to form theoretical generalizations and conclusions. Graphic and tabular methods are used to visualize the results.Findings. Key global trends in the development of agriculture are identified, in particular the impact of demographic changes, climate challenges, resource constraints and transformation of food markets.The current state of the agro-industrial sector of Ukraine in the context of military challenges is analysed, in particular the dynamics of its share in GDP, production, profitability and investment activity. The presence of structural imbalances, interregional inequalities and limited access to financial resources was established.A comparative analysis of the agricultural sector of Ukraine and Poland was carried out, which allowed to identify differences in the management structure, level of state support, efficiency of resource use and orientation on added value.The need to introduce adaptation mechanisms is substantiated, in particular digitalization, development of processing, improvement of financial support, greening of production and harmonization of legislation with EU requirements.Originality. Theoretical approaches to determining the directions of adaptation of agro-industrial enterprises to global changes based on a combination of economic, technological, environmental and institutional factors, as well as systematization of EU practices (using the example of Poland) for their implementation in Ukraine, have been further developed.Practical value. The obtained results can be used in the formation of state agricultural policy, development of strategies for the development of agro-industrial enterprises, as well as in the process of adapting the national agricultural sector to the requirements of European integration. The proposed directions will contribute to increasing the competitiveness, sustainability and innovativeness of agricultural production in Ukraine. Key words: agricultural enterprises, global changes, sustainability, development, adaptation of enterprises, state support, enterprise support instruments, digitalization, reforms, climate challenges.
Keywords: agricultural enterprises; global changes; sustainability; development; adaptation of enterprises; state support; enterprise support instruments; digitalization; reforms; climate challenges